Exploring Global Trends in Whistleblowing Intention: A Two-Decade Systematic Bibliometric Review in Accounting and Governance - Putu Novia Hapsari Ardianti; Ni Luh Putu Wiagustini; Ni Made Dwi Ratnadi; Ni Putu Sri Harta Mimba (Jurnal Dinamika Akuntansi dan Bisnis, 2025)
This study aims to map global trends and key themes in whistleblowing intention research using a bibliometric systematic literature review approach. Employing co-word analysis, bibliographic coupling, co-author analysis, and co-country analysis, the study utilized VOSviewer and R Studio for visual mapping. A total of 1,722 articles published between 2006 and 2025 were retrieved from the Scopus and Web of Science databases, of which 141 were selected through the PRISMA protocol. The results highlight the significant role of culture in shaping reporting intentions. In Western countries, where individualistic values predominate, moral courage primarily drives the decision to report wrongdoing. By contrast, in Eastern countries with collectivistic cultures, social pressure and the prioritization of group harmony exert stronger influence than individual actions. These findings illustrate how whistleblowing intention is shaped by the interplay of individual, organizational, and cultural factors that vary across contexts.